1975
DOI: 10.1073/pnas.72.5.1843
|View full text |Cite
|
Sign up to set email alerts
|

Folding of the DNA double helix in chromatin-like structures from simian virus 40.

Abstract: Relaxed circular, covalently closed simian virus 40 DNA molecules were associated with the four histones that are present in virions. In electron micrographs the resulting complexes appear twisted, with globular structures (nucleosomes) along the DNA. Incubation with an untwisting extract converts the twisted complexes to relaxed structures. Extraction of the DNA from the relaxed complexes yields supercoiled molecules. The number of superhelical turns in these molecules corresponds to the number of nucleosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
341
1
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(364 citation statements)
references
References 31 publications
17
341
1
1
Order By: Relevance
“…Indeed, Kodgire et al reported that insertion of the nucleosome positioning sequence, which is tightly folded by the nucleosome, into the variable region of the Ig light chain gene reduces SHM in and around the inserted region (30). Another explanation involves the fact that unwinding DNA from nucleosome produces one negative supercoil (31). It is known that excessive negative supercoil behind the transcription elongation complex tends to form irregular DNA structures called non-B DNA (3,32), which is proposed to be the substrate for DNA-cleaving enzymes such as DNA topoisomerase 1 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Kodgire et al reported that insertion of the nucleosome positioning sequence, which is tightly folded by the nucleosome, into the variable region of the Ig light chain gene reduces SHM in and around the inserted region (30). Another explanation involves the fact that unwinding DNA from nucleosome produces one negative supercoil (31). It is known that excessive negative supercoil behind the transcription elongation complex tends to form irregular DNA structures called non-B DNA (3,32), which is proposed to be the substrate for DNA-cleaving enzymes such as DNA topoisomerase 1 (6).…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray data showed that the double helix of DNA in a nucleosome is wound (about a histone core) into about two turns of a (shallow) superhelix, whereas measurements on closed, circular DNA extracted from SV40 chromatin gave a degree of supercoiling nearer one superhelical turn per nucleosome (2). However, as first realised by Crick (3), what was being measured in the physico-chemical experiments was not the "number of supercoils", but the change in the linkage number of DNA (i.e.…”
Section: The Linkage Number Problem and The Screw Of Dnamentioning
confidence: 99%
“…4) The present study demonstrates that the SV40 viral transcription complex (VTC) can synthesize long RNA transcripts under conditions in which protein does not dissociate from the transcriptionally active chromatin. Electron microscopic and biochemical studies have revealed a close similarity between the structure of SV40 and cellular chromatin (4)(5)(6)(7)(8)(9)(10). On the basis of sedimentation rate (23) and density in CsCl (Fig.…”
Section: H-rna ( ); 14c-vtc (---); 14c-dna (---)mentioning
confidence: 99%
“…The viral complex has been shown by electron microscopic (4)(5)(6) and biochemical (5,(7)(8)(9)(10) analyses to possess a structure which closely resembles that of cellular chromatin. There is an average of 21 beads (nucleosomes) per SV40 genome, each having a diameter of ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation